Phylogenetic Reconstruction, Morphological Diversification and Generic Delimitation of Disepalum (Annonaceae). - Pui-Sze Li; Daniel C Thomas; Richard M K Saunders (PLoS ONE, 2015)
Taxonomic delimitation of Disepalum (Annonaceae) is contentious, with some researchers favoring a narrow circumscription following segregation of the genus Enicosanthellum. We reconstruct the phylogeny of Disepalum and related taxa based on four chloroplast and two nuclear DNA regions as a framework for clarifying taxonomic delimitation and assessing evolutionary transitions in key morphological characters. Maximum parsimony, maximum likelihood and Bayesian methods resulted in a consistent, well-resolved and strongly supported topology. Disepalum s.l. is monophyletic and strongly supported, with Disepalum s.str. and Enicosanthellum retrieved as sister groups. Although this topology is consistent with both taxonomic delimitations, the distribution of morphological synapomorphies provides greater support for the inclusion of Enicosanthellum within Disepalum s.l. We propose a novel infrageneric classification with two subgenera. Subgen. Disepalum (= Disepalum s.str.) is supported by numerous synapomorphies, including the reduction of the calyx to two sepals and connation of petals. Subgen. Enicosanthellum lacks obvious morphological synapomorphies, but possesses several diagnostic characters (symplesiomorphies), including a trimerous calyx and free petals in two whorls. We evaluate changes in petal morphology in relation to hypotheses of the genetic control of floral development and suggest that the compression of two petal whorls into one and the associated fusion of contiguous petals may be associated with the loss of the pollination chamber, which in turn may be associated with a shift in primary pollinator. We also suggest that the formation of pollen octads may be selectively advantageous when pollinator visits are infrequent, although this would only be applicable if multiple ovules could be fertilized by each octad; since the flowers are apocarpous, this would require an extragynoecial compitum to enable intercarpellary growth of pollen tubes. We furthermore infer that the monocarp fruit stalks are likely to have evolved independently from those in other Annonaceae genera and may facilitate effective dispersal by providing a color contrast within the fruit.